Analisis Usaha Peternakan Sapi Perah ABC di Cisarua Bogor Jawa Barat: ABC Dairy Farm Business Analysis at Cisarua, Bogor, West Java - Munawarah, Mawaddah; Ayuningtyas, Gilang; Sembada, Pria (Politeknik Pertanian Bogor, 2024)
The ABC dairy farm is one of the farms that have been incorporated into the dairy cooperative business system. It is necessary to conduct a study related to business analysis, with a particular focus on profit analysis in the current context, marketing development based on the principles of the marketing mix, and a SWOT analysis. The objective of this study is to evaluate the financial performance of ABC farms and to identify potential avenues for business growth through enhancements in marketing strategies and an examination of internal and external factors influencing business outcomes through a SWOT analysis. The research method employed is descriptive and quantitative and qualitative. Data were collected through in-depth interviews with farm owners and relevant stakeholders, direct observation at the farm location, and a review of the relevant literature. The financial analysis of the ABC Dairy Farm indicates that it continues to generate profits in each production period, as evidenced by the positive results observed. The Internal and External Factor Evaluation (IFE, EFE) matrix analysis yielded a value of 3,53, indicating a robust capacity to capitalize on opportunities and leverage strengths in the face of potential threats and business weaknesses. The business development of ABC Dairy Farm, as indicated by the results of the I-E matrix analysis, is situated within quadrant I, indicating growth and development. Based on these results, the recommended alternative strategies are market development and product development.